Mathematical Literacy on Statistical Measures A Design Research Study - Büscher, Christian (Dortmunder Beiträge zur Entwicklung und Erforschung des Mathematikunterrichts ;, 2018)
In most countries, only very limited time resources are available for statistics education within mathematics education. Thus, statistics education research needs to develop teaching-learning arrangements that are compact and applicable to classrooms. Christian Büscher designs and investigates a compact teaching-learning arrangement which aims at mathematical and reflective knowledge about statistics. Central results include the specification of the learning content of statistical measures, an empirical reconstruction of students' learning processes towards statistical measures, and the identification of students' situated reflections about mathematics within their learning processes. Contents Mathematical Literacy in Statistics Specifying the Mathematizing Concept of Statistical Measure Reflective Concepts and Activities as a Conceptualization of Reflective Knowledge Designing a Compact Teaching-Learning Arrangement Identifying Students' Situative Reflective Concepts Target Groups Researchers, academics, and scholars of mathematics, statistics, and didactics Teachers of mathematics and statistics The Author Christian Büscher investigates learning processes in statistics through Design Research at Technical University of Dortmund, Germany. The Editors The series Dortmunder Beiträge zur Entwicklung und Erforschung des Mathematikunterrichts is edited by Stephan Hußmann, Marcus Nührenbörger, Susanne Prediger und Christoph Selter.